Actual State of Recreation and Recuperation of Children in Ukraine - Kulykovskyi, Sergii (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2016)
Development areas of child recreation and health are the subject of social responsibility of the state, maintains the health of the Ukrainian nation, solves a large number of educational problems. Statistical analysis conducted by Department of rehabilitation and sanatorium - resort treatment Ministry of Social Policy of Ukraine, the State Register of Ukraine camps and laboratories geolocation and tourism Kiev National University of Taras Shevchenko makes it possible to identify the main trends in children’s health system in Ukraine. The main trends are: significant reduction system fixed camps, camps with increasing day stay, the increasing number of children who receive services system of children’s health and recreation. Questioning of Directors of various camps Ukraine makes it possible to identify the main problems and achievements of the system of children’s health in Ukraine. The most important problems can be grouped into two groups: social - economic - associated with the financial condition of the population and business conditions generally, and social - pedagogical that lead educational work and nuances of children’s activities.